Social Media Usage and Academic Performance of Undergraduate Science Education Students: Evidence From Universities in Rivers State, Nigeria - J. OWO, Wisdom (International Journal on Integrated Education, 2025)
The rise of information and communication technology, particularly social media, has profoundly shaped human behaviour due to its global acceptance and relevance in various areas of life. Students, in particular, are increasingly active on social networking platforms, often displaying inappropriate usage, such as during lectures or in places of worship. This study explores how social media usage affects the academic performance of science education students at universities in Rivers State, Nigeria. A sample of 1,026 students was randomly chosen from Ignatius Ajuru University of Education (IAUE) and Rivers State University (RSU) to complete a questionnaire designed by the researcher. Results of the study revealed that students primarily use social media for communication (mean = 3.89), with Facebook being the most frequently used platform for academic purposes (mean = 3.92) and skype the least used (mean = 1.03). The result also show that while social media has both positive and negative effects on academic performance, poor time management and unregulated use significantly contribute to the negative impacts. To address these issues, students are encouraged to adopt effective time management strategies and prioritize their responsibilities and social media usage. Additionally, students should focus on leveraging social media to enhance their academic outcomes rather than engaging in excessive or nonessential activities on social media.